Radiotherapy for tumors of the mediastinum – state of the art - Kantzou, Ioanna; Sarris, Georgios; Kouloulias, Vasileios; Abatzoglou, Ioannis; Leivaditis, Vasileios; Grapatsas, Konstantinos; Koletsis, Efstratios; Papatriantafyllou, Athanasios; Dahm, Manfred; Mulita, Admir; Mulita, Francesk; Baltayiannis, Nikolaos (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2023)
Mediastinal tumors encompass a diverse range of malignancies, originating within or spreading to the mediastinum. The administration of radiotherapy within the anatomical confines of the mediastinum presents unique challenges owing to the close proximity of critical organs, including the heart, lungs, esophagus, and spinal cord. However, recent progress in imaging techniques, treatment modalities, and our understanding of tumor biology has significantly contributed to the development of effective and safe therapeutic strategies for mediastinal diseases. This review article aims to explore the latest innovations in radiotherapy and their practical applications in the management of mediastinal tumors, with a primary focus on lymphomas, thymomas, and thymic carcinomas. By examining these advancements, we seek to provide valuable insights into the current state of the art in radiotherapy for mediastinal malignancies, ultimately fostering improved patient outcomes and clinical decision-making.